1999
DOI: 10.1002/hep.510290108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sho-saiko-to, a japanese herbal medicine, on hepatic fibrosis in rats

Abstract: It has been shown that lipid peroxidation is associated with hepatic fibrosis and stellate cell activation. Shosaiko-to (TJ-9) is an herbal medicine, which is commonly used to treat chronic hepatitis in Japan, although the mechanism by which TJ-9 protects against hepatic fibrosis is not known. As a result, we assayed the preventive and therapeutic effects of TJ-9 on experimental hepatic fibrosis, induced in rats by dimethylnitrosamine (DMN) or pig serum (PS), and on rat stellate cells and hepatocytes in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
189
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(195 citation statements)
references
References 57 publications
4
189
0
1
Order By: Relevance
“…Indeed, the 12-LOX inhibitor baicalein is the main component of an herbal medicine (Sho-Saiko-To) commonly administered in Asian countries to outpatients with chronic hepatitis. 62 Our findings suggest that such compounds may also offer new potential strategies in the pharmacological treatment of AD.…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, the 12-LOX inhibitor baicalein is the main component of an herbal medicine (Sho-Saiko-To) commonly administered in Asian countries to outpatients with chronic hepatitis. 62 Our findings suggest that such compounds may also offer new potential strategies in the pharmacological treatment of AD.…”
Section: Discussionmentioning
confidence: 77%
“…A later prospective, randomized (albeit nonblind) study by Oka et al [410] could elucidate the use of TJ-9 in preventing the development of HCC in patients with cirrhosis, particularly in patients without HBsAg. Successive studies continued to confirm that TJ-9 could protect experimental liver injury caused by D-galactosamine and liver fibrosis by inhibition of lipid peroxide formation in liver cells [411,412].…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 96%
“…Recently, it has been proposed that plant-derived antioxidants may emerge as potential antifibrotic agents (Gebhardt, 2002;Schuppan et al, 1999). For example, it has been reported that herbal extracts such as Sho-saiko-to (TJ-9) (Shimizu et al, 1999), silymarin (Boigk et al, 1997) and Inchin-ko-to (TJ-135) (Sakaida et al, 2003) can inhibit HSC activation and thereby exert antifibrotic effects in animals.…”
Section: Introductionmentioning
confidence: 99%